2016
DOI: 10.5539/jsd.v9n3p192
|View full text |Cite
|
Sign up to set email alerts
|

Uganda’s Revealed Comparative Advantage in COMESA

Abstract: Most recently, Uganda increased its trade engagements with COMESA as demonstrated by its submission of accession instruments to COMESA Secretariat in order to access the Free Trade Area (FTA). It is envisaged that trade with COMESA can compensate for the low export demand elsewhere by enabling diversification of the export basket and facilitating value addition to traditional exports. It is also expected to enhance producer competitiveness and consumer welfare. Full exploitation of this requires information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another study that attempts to employ the RCA is the study of Katunze and Kuteesa (2016) the study examined RCA by using Symmetric Index (SI) which was first engineered by Laursen (1998) to account for the asymmetry problem. The study evaluated the stability of Uganda's revealed comparative advantage in Common Market for Eastern and Southern Africa (COMESA).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Another study that attempts to employ the RCA is the study of Katunze and Kuteesa (2016) the study examined RCA by using Symmetric Index (SI) which was first engineered by Laursen (1998) to account for the asymmetry problem. The study evaluated the stability of Uganda's revealed comparative advantage in Common Market for Eastern and Southern Africa (COMESA).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…There are a lot of similarities in the EAC region in regards endowments however, and value addition would be a key ingredient to maintaining Uganda's benefits from trade. The diversification of the export basket and facilitating value addition to traditional exports is seen as a means to increase Uganda's export demand beyond east Africa, to the COMESA for instance (Katunze & Kuteesa, 2016…”
Section: Country Similaritiesmentioning
confidence: 99%
“…As a result, comparative advantage is a primary source of cross-country trade flows, and countries should align their internal trade policies with their comparative advantage when formulating policies. Studies on comparative advantage in East Africa have tended to focus on individual countries and specific commodities or sectors (see for example, Katunze and Kuteesa, 2016;Mkenda, 2014;Ndayitwayeko et al, 2014;Were and Odongo, 2019), rather than looking at which product groups the EAC members have comparative advantage within the Community and how comparative advantage has evolved over time. As a result, this study adds to our understanding of how trade structure has changed following the revival of the Community by not only examining the product groups in which the countries have comparative advantage, but also how it has changed since its revival.…”
Section: Introductionmentioning
confidence: 99%